”La vile multitude” – Marx og Pariserkommunen - Beck Holm, Andreas (Slagmark - Tidsskrift for idéhistorie, 2018)
’The VILE MULTITUDE’ - MARX AND THE PARIS COMMUNE The entire purpose of Marx’s work is to enable the working class to act as a revolutionary subject, i.e. as its own liberator, destined to overthrow capitalism. However, this paper demonstrates that this view, which has political validity, is supplemented by another more nuanced and more theoretically interesting understanding of revolutionary upheavals in Marx’s work. This more subtle approach is found particularly in his political analyses, and the paper specifically interprets his writings on the Paris Commune in this light. It is argued that in Marx’s analysis of the actual events, it is not the working classes of Paris that make the revolution. Rather, the revolution is triggered by a series of extraordinary circumstances, and by external agents. It produces an undecidedness, here referred to as a multitude, which is only après coup seized and defined by the working classes. Finally, the paper details how this reading has consequences for a Marxist understanding of politics in general and revolutionary upheavals in particular.